Existence Results for ψ-Hilfer Fractional Integro-Differential Hybrid Boundary Value Problems for Differential Equations and Inclusions - Chanakarn Kiataramkul; Sotiris K. Ntouyas; Jessada Tariboon (Advances in Mathematical Physics)
In this research work, we study a new class of ψ-Hilfer hybrid fractional integro-differential boundary value problems with nonlocal boundary conditions. Existence results are established for single and multivalued cases, by using suitable fixed-point theorems for the product of two single or multivalued operators. Examples illustrating the main results are also constructed.